Aplikasi Simpan Pinjam Koperasi Karyawan Universitas Kristen Petra Berbasis Website - Ivan Eko Novianto; Andreas Handojo; Anita Nathania Purbowo (Jurnal Infra, 2019)
Petra Christian University Cooperative (UK Petra) is a cooperative that has 2 businesses namely self-service and cooperatives. The cooperative itself has 2 programs, namely savings and loans. At present the UK Petra cooperative only has programs offline. The programs owned by the UK Petra cooperative can only be accessed by cooperative officials and some activities such as member registration, periodic deposit applications, long-term submissions and loan applications are still using paper. In addition members if you want to know information such as periodic deposit balances, how much loans or installments the remaining is very difficult to know because members must go or ask or call the cooperative management. This is felt to be very less effective in disseminating or facilitating information.Seeing this problem, then in this thesis a website information system will be created. This website can do such as submitting periodic deposits, submitting long-term deposits, applying for loans, can see cooperative financial information.the final result of the thesis is that the system has been able to send notifications online via email based on internet speed, the system has been able to submit applications online, the system has been able to perform periodic savings calculations, self-help time deposits and loans and the system has been able to help the cooperative in looking at financial conditions members in terms of savings.